Scheduling Uses the Blynk 2.0 Automations Feature for Effective Ornamental Fish Feeding - Haryansyah, Haryansyah; Hadriansa, Hadriansa; Ardiansyah, Riswan (Pandawan, 2023)
Maintenance of ornamental fish can not be separated from the importance of regular feeding. Feeding which is still done manually will of course confiscate time and requires patience. However, the problem is when traveling that it doesn't Allows manual feeding. Matter this requires a system or tool that can provide fish feed automatically based on a schedule which is determined. One that can be used is with create Internet of Things (IoT)-based devices. There have been many developments in IoT-based devices gave birth to a variety of features that can be utilized in create automation tools in everyday life. Wrong one of which is a feature on the Blynk 2.0 application. on this application there is one feature that can be utilized in the process scheduling to perform one particular activity that very easy for users without having to be difficult to make a program commonly known as Automation feature. This feature will work continuously periodically according to a predetermined schedule. On research this will take advantage of these features in the manufacture of tools automatic fish feeding automation. scheduling feeding fish will utilize automation features at the same time can be monitored when the last feed was given. This study utilizes the NodeMCU ESP8266 as main controller and servo motor as driving tool feeder. The tool will be connected to the Blynk application via Wi-Fi network.